Traditions in world cinema - Badley, Linda; Palmer, R. Barton, 1946-; Schneider, Steven Jay, 1974- (Edinburgh : Edinburgh University Press, 2006)
The core volume in the Traditions in World Cinema series, this book brings together a colourful and wide-ranging collection of world cinematic traditions - national, regional and global - all of which are in need of introduction, investigation and, in some cases, critical reassessment. Topics include: German expressionism, Italian neorealism, French New Wave, British new wave, Czech new wave, Danish Dogma, post-Communist cinema, Brazilian post-Cinema Novo, new Argentine cinema, pre-revolutionary African traditions, Israeli persecution films, new Iranian cinema, Hindi film songs, Chinese wenyi pian melodrama, Japanese horror, new Hollywood cinema and global found footage cinema. Key Features Includes a preface by Toby Miller. Each chapter covers a key world cinema tradition and is written by an expert in the field: Roy Armes, Nitzan Ben-Shaul, Peter Bondanella, Corey Creekmur, Adrian Danks, Peter Hames, Randal Johnson, Robert Kolker, Myrto Konstantarakos, Jay McRoy, Negar Mottahedeh, Richard Neupert, Christina Stojanova, J.P. Telotte, Stephen Teo. Traditions are examined from a wide range of views and include historical, social, cultural and industrial perspectives.
German expressionism / J.P. Telotte -- Italian neorealism / Peter Bondanella -- The French new wave / Richard Neupert -- The British new wave / R. Barton Palmer -- The Czechoslovak new wave / Peter Hames -- Danish dogma / Linda Badley -- Post-Communist cinema / Christina Stojanova -- Post-cinema novo Brazilian cinema / Randal Johnson-- New Argentine cinema / Myrto Konstantarakos -- Early cinematic traditions in Africa / Roy Armes -- Israeli persecution films / Nitzan Ben-Shaul -- New Iranian cinema / Negar Mottahedeh -- Popular Hindi cinema and the film song / Corey Creekmur -- Chinese melodrama / Stephen Teo -- Japanese horror cinema / Jay McRoy -- The "new" American cinema / Robert Kolker -- The global art of found footage cinema / Adrian Danks.
Includes filmographies, bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Motion pictures -- History; Motion pictures -- Reviews; Cinéma -- Histoire; Cinéma -- Comptes rendus; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Motion pictures; Film; Music, Dance, Drama & Film; Motion pictures; History; Reviews